Analysis Of Blended Learning Models in Class V Science Subjects at SD KIP Maccini - Alannasir, Wahyullah (Journal of Research and Multidisciplinary, 2024)
The objectives of this study are to; 1) Analyzing the learning process during the Pandemic, 2) Evaluating the application of the Blended Learning Learning Model in Class V Science Subjects, and, 3) Comparing Supporting and Inhibiting Factors for the application of the Blended Learning Learning Model at SD KIP Maccini. This research is a phenomenological research using a paedagogy approach. while data collection is taken through interviews, observations and documentation. The results of this study show that the learning process is divided into 2 learnings, namely online learning and face-to-face learning, because it uses a blended learning model, and the application of this model provides opportunities for students and teachers to carry out learning independently and create a space for interaction both between teachers and students and between students and students. Supporting factors for this study are the availability and affordability of resources, the ability of teachers to manage classes, teachers' skills in operating smartphones and the physical condition of students. Meanwhile, the inhibiting factor in the application of blended learning models is an unstable internet connection.